INTEGRATION OF STRATEGIC MANAGEMENT AND ISLAMIC SPIRITUALITY IN REALIZED GOOD ISLAMIC GOVERNANCE AT NURUL QADIM ISLAMIC BOARDING SCHOOL - Rifka Jannatul Firdausiyah; Robert Edy Sudarwan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study analyzes the integration of strategic management and Islamic spirituality in building Good Islamic Governance at the Nurul Qadim Islamic Boarding School. In the digital era and educational competition, Islamic boarding schools are required not only to uphold Islamic values but also to build professional and adaptive governance. This research used a descriptive qualitative approach with a case study method. Data were obtained through in-depth interviews, participant observation, and documentation. The results indicate that using a management strategy based on Islamic spirituality increases the accountability, transparency, and effectiveness of educational programs. Islamic values such as amanah (trustworthiness), ihsan (goodness), and ikhlas (sincerity) guide every stage of the strategy, from planning to evaluation. The institution's vision and mission serve as a moral compass for governance, and a SWOT analysis is used to identify the institution's strengths and challenges. This integration demonstrates that this management system balances worldly and hereafter orientations.